I need to find the derivative of the following.. g(t) = ln(t^{2}e^{-t^2}) = (ln e = 1, right?) g '(t)= g '(t)= According to my textbook though, I should have gotten this... Where is the t^{2 }coming from?
Follow Math Help Forum on Facebook and Google+
Originally Posted by astuart I need to find the derivative of the following.. g(t) = ln(t^{2}e^{-t^2}) = (ln e = 1, right?) g '(t)= g '(t)= According to my textbook though, I should have gotten this... Where is the t^{2 }coming from?
Originally Posted by Prove It Ah. Is it from this?? Basically, to subtract fractions they must have the same denominator - therefore to get 2t to be 2t / t, it has to be multiplied by t?
View Tag Cloud